Improving Young Learners’ Vocabulary Through Total Physical Response Method - Dini Hasanul Awaliah; Fovi Sriyuliawati; Rinaepi (Universitas Islam Al-Ihya Kuningan, 2024)
The aim of this study is to enhance the English vocabulary of young learners through the Total Physical Response method in KB Al-Hikmah. The research follows a collaborative classroom action research design. The subjects of the study are 13 children aged 5–6 who are part of Class B. The data collection methods include interviews, observations, and tests. The data analysis used in this research is a qualitative and quantitative descriptive analysis. The result of the study showed that there was improvement in young learners’ vocabulary mastery. It can be proven from the results of the observation sheets that there was a significant improvement in the response of young learners from cycle 1 to cycle 2. In cycle 1, the majority of students actively participated (61.5%), while a smaller proportion were less active (7.7%), and a significant majority were very active (30.5%). However, in cycle 2, there was a notable increase in the number of engaged students (23.07%) and a substantial majority of very active students (76.93%). The response of young learners during the teaching and learning process demonstrates their active participation in the classroom. Furthermore, there was an improvement in the mean writing scores of the young learners. In the preliminary study, only 46.15% of the class met the success indicator, while in the first cycle, the percentage increased to 67.7%, and in the second cycle, it reached an impressive 85.1% success indicator. The results obtained, which are valid and acceptable, show that the implementation of the Total Physical Response method through play has successfully improved the English vocabulary of young learners in Class B of KB Al-Hikmah.